Focal adhesion kinase confers pro‐migratory and antiapoptotic properties and is a potential therapeutic target in Ewing sarcoma. Issue 2 (21st December 2019) - Steinestel, Konrad; Trautmann, Marcel; Jansen, Esther‐Pia; Dirksen, Uta; Rehkämper, Jan; Mikesch, Jan‐Henrik; Gerke, Julia S.; Orth, Martin F.; Sannino, Giuseppina; Arteaga, Maria‐Francisca; Rossig, Claudia; Wardelmann, Eva; et al.
Abstract : Oncogenesis of Ewing sarcoma (EwS), the second most common malignant bone tumor of childhood and adolescence, is dependent on the expression of chimeric EWSR1‐ETS fusion oncogenes, most often EWSR1‐FLI1 (E/F). E/F expression leads to dysregulation of focal adhesions (FAs) enhancing the migratory capacity of EwS cells. Here, we show that, in EwS cell lines and tissue samples, focal adhesion kinase (FAK) is expressed and phosphorylated at Y397 in an E/F‐dependent way involving Ezrin. Employing different EwS cell lines as in vitro models, we found that key malignant properties of E/F are mediated via substrate‐independent autophosphorylation of FAK on Y397. This phosphorylation results in enhanced FA formation, Rho‐dependent cell migration, and impaired caspase‐3‐mediated apoptosis in vitro . Conversely, treatment with the FAK inhibitor 15 (1, 2, 4, 5‐benzenetetraamine tetrahydrochloride (Y15) enhanced caspase‐mediated apoptosis and EwS cell migration, independent from the respective EWSR1‐ETS fusion type, mimicking an anoikis‐like phenotype and paralleling the effects of FAK siRNA knockdown. Our findings were confirmed in vivo using an avian chorioallantoic membrane model and provide a first rationale for the therapeutic use of FAK inhibitors to impair metastatic dissemination of EwS. Abstract : In Ewing sarcoma (EwS) cells, EWSR1‐FLI1‐dependent expression of Ezrin contributes to autophosphorylation of focal adhesion kinase (FAK) on tyrosine 397. This impairs apoptosis and detachment‐dependent cell death (anoikis) and enhances focal adhesion formation and migratory capacity of EwS. Since Y397 autophosphorylation can effectively be targeted by FAK inhibitor 15 (1, 2, 4, 5‐benzenetetraamine tetrahydrochloride (Y15), FAK might represent a valuable target for antimetastatic pharmacotherapy in EwS.